Blood parameters and electroencephalographic responses of goats to slaughter without stunning - Sabow, A. B.; Goh, Y. M.; I., Zulkifli; Sazili, A. Q.; Kaka, U.; Kadi, M. Z.; Ebrahimi, M.; Nakyinsige, K.; Adeyemi, K. D. (Elsevier BV, 2016)
The study compared changes in blood biochemistry, hormonal and electroencephalographic indices associated with possible noxious stimuli following neck cut slaughter in conscious, non-anaesthetized versus minimally-anaesthetized goats. Ten male Boer crossbreed goats were assigned into two groups and subjected to either slaughter conscious without stunning (SWS) or slaughter following minimal anaesthesia (SMA). Hormonal responses and changes in electroencephalographic (EEG) parameters were not influenced by slaughter method. The SWS goats had higher glucose and lactate than did SMA goats. It can be concluded that the noxious stimulus from the neck cut is present in both conscious and minimally anaesthetized goats. The application of slaughter without stunning causes changes in the EEG activities that are consistent with the presence of post slaughter noxious sensory input associated with tissue damage and would be expected to be experienced as pain in goats.